PENGARUH JUMLAH PENDUDUK DAN UMUR HARAPAN HIDUP TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT - Egi Anggara; M Joni; Ahmadi Ahmadi; Kurniasih Setyagustina (Manajemen Keuangan Syariah, 2022)
The background of this research arises from the interest of researchers to see what are the benchmarks to determine the good and bad of the welfare of the community, especially in the area of origin of the researcher.  Arguments or opinions that say large population causes big problems as well such as welfare problems, where the relationship with the presence of the population and the number of health facilities is an interesting discussion in looking at the welfare of the community. The research method used is a quantitative method, using time series data sourced from secondary data. The data were obtained and researched at the Central Bureau of Statistics of Merangin Regency. Data analysis using SPSS 26.0 program. The results of the data processing show that the researcher's hypothesis is accepted on the population variable, where the level of community welfare has an influence on the population. The rejection of the hypothesis for the effect of life expectancy on the level of community welfare occurs because of the lack of data. The results of this study are expected to be input and support in making people's economic development policies in the Merangin Regency area in accordance with existing Islamic law.